ANALYSIS OF TIMELINESS OF FINANCIAL REPORTING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Pebruary, Silviana (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2021)
This study aims to analyze the factors that affect the timeliness of financial reporting in manufacturing companies in the transportation subsector listed on the Indonesia Stock Exchange for the 2016-2020 period, based on previous research, these factors are profitability, liquidity, solvency, and size. The type of research carried out is a quantitative approach. Hypothesis testing is carried out using binary logistic regression, which is used because there are variables used in the form of dummy (binary). Logistic regression consists of categories 1 and 0. The results show that profitability, liquidity, and company liquidity have no significant effect on the timeliness of financial statement submission. While solvency has a significant effect on the possibility of timeliness of financial statements.